APLIKASI TEMATIS METODE MAWDU’I HADIS TENTANG ORANG-ORANG MUKMIN LAKSANA SATU BANGUNAN - Muhammad Qomarullah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
The author will increase the theme of hadiths related to traditions related to one believer and another brother. This research requires a deep understanding using a variety of approaches, both textually, intertextually, and contextually. Not all traditions are valid from the Messenger of Allah (qat'i al-wurud), so takhrij al-Hadith (proof of fidelity) is needed. Mawdu'i method could be relied upon to solve problems that exist in society, because this method provides an opportunity for someone to try to provide answers to problems taken from the instructions of the Qur'an and Hadith. The application of this method is by determining the hadiths related to "One believer is like a building", issuing related traditions (Takhrij al-Hadith), examining sanad matn and Mukharrij, critically analyzing sanad and matn, and concludes from the aspects of text, context and contextualization of a hadith that is related to "Muslims are like buildings".